The complete guide to digital illustration - Caplin, Steve, ....-; Banks, Adam, ....- (Lewes : Ilex, 2003)
Samenvatting:Caplin and Banks present a lively primer on digital illustration thatcovers digital painting, drawing, illustration, animation, and more. Thispicture-rich resource boasts a glossary, bibliography, and listing offurther readings, ensuring that digital designers who are manipulatingphotos, doing 3-D modeling, and exploring the complexities of stackingand layers in illustration will have a wealth of useful instruction andinformation at hand.
Keywords: Digitale technieken